On the use of nanoindentation for cementitious materials - Constantinides, Georgios; Ulm, Franz Josef; Van Vliet, Krystyn J. (My University, 2003)
Recent progress in experimental and theoretical nanomechanics opens new venues in materials science for the nano-engineering of cement-based composites. In particular, as new experimental techniques such as nanoindentation provide unprecedented access to micro-mechanical properties of materials, it becomes possible to identify the mechanical effects of the elementary chemical components of cement-based materials at the scale where physical chemistry meets mechanics, including the properties of the four clinker phases, of portlandite, and of the C-S-H gel. In this paper, we review some recent results obtained by nanoindentation, which reveal that the C-S-H gel exists "mechanically" in two different forms, a low-density form and a high-density form, which have different mean stiffness and hardness values and different volume fractions. While the volume fractions of the two phases depend on mix proportions, the mean stiffness and hardness values do not change from one cement-based material to another; instead they are intrinsic properties of the C-S-H gel.
Keywords: Composite materials; Hardness; Materials science; Mechanics; Nanostructured materials